Number of Endoscopic Retrograde Cholangiopancreatography Procedures Required for Short Biliary Cannulation Time - Koichiro Mandai; Koji Uno; Yasutoshi Fujii; Takuji Kawamura; Kenjiro Yasuda (Gastroenterology Research and Practice)
Background. Several previous studies assessed the competence in endoscopic retrograde cholangiopancreatography (ERCP) using the bile duct cannulation success rate. However, the cannulation time is also important, because a long cannulation time was reported to be a risk factor for post-ERCP pancreatitis. Aim. To determine the number of ERCP procedures required for short cannulation time of the bile duct. Methods. We retrospectively analyzed 605 ERCP procedures performed for bile duct cannulation in patients with native papilla at our institution between March 2012 and December 2015. The successful procedures were divided into 2 groups: group L and group S (cannulation time>15 minutes and ≤15 minutes, resp.). An analysis of the relationship among the biliary cannulation time, ERCP experience, and other factors was then conducted. Results. Multivariate analysis showed that the ERCP experience of ≤300 procedures (odds ratio, 2.080; 95% confidence interval, 1.337–3.142; P=0.001) and malignant biliary stricture due to pancreatic cancer (odds ratio, 1.912; 95% confidence interval, 1.072–3.412; P=0.028) were found to be significantly associated with a cannulation time of >15 minutes. Conclusions. Our findings suggested that an ERCP experience of ≤300 procedures and malignant biliary stricture due to pancreatic cancer were associated with prolonged biliary cannulation time.